The role of diplomatic correspondence in the Mamluk-Frankish war (Baybar’s letter to the ruler of Tripoli is a model) - حسن غادة (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The diplomatic correspondence is one of the means used by the Mamluks in their relations with other powers, including the Franks, and these messages played an important role in the Mamluk-Frankish war in the Levant. The Mamluks sultans used them as a weapon of psychological warfare against the enemy in addition to their wartime military arsenal. By analyzing the content of one of these messages, this research aims to provide a glimpse of the image that Sultan Baybars viewed of his opponent Bohemand VI. This letter presents an important and clear view of Mamluk ideological speeches and political incidents at that point. The research also shows the use of the writers of the Diwan al-Insha’ by the sultans to write these correspondences, in which the language, graphic images and recorded prose used to make the greatest impact on the recipient, thus forming an archive of eloquence and models preserved in the establishment office for use when needed.